Neuroprotective Effects of GV1001 in Animal Stroke Model and Neural Cells Subject to Oxygen-Glucose Deprivation/Reperfusion Injury - Kwon, Hyuk Sung; Kim, Ye Eun; Park, Hyun-Hee; Son, Jeong-Woo; Choi, Hojin; Lee, Young Joo; Kim, Hyun Young; Lee, Kyu-Yong; Koh, Seong-Ho (Journal of stroke, 2021)
Background and Purpose Previous studies have revealed the diverse neuroprotective effects of GV1001. In this study, we investigated the effects of GV1001 on focal cerebral ischemia-reperfusion injury (IRI) in rats and oxygen-glucose deprivation/reoxygenation (OGD/R)-induced injury in neural stem cells (NSCs) and cortical neurons. Methods Focal cerebral IRI was induced by transient middle cerebral artery occlusion (MCAO). Brain diffusion-weighted imaging (DWI) was performed 2 hours after occlusion, and a total of 37 rats were treated by reperfusion with GV1001 or saline 2 hours after occlusion. Fluid-attenuated inversion recovery (FLAIR) magnetic resonance imaging, immunohistochemistry, and neurobehavioral function analyses were performed. Additionally, OGD/R-injured NSCs and cortical neurons were treated with different GV1001 concentrations. Cell viability, proliferation, migration, and oxidative stress were determined by diverse molecular analyses. Results In the stroke model, GV1001 protected neural cells against IRI. The most effective dose of GV1001 was 60 μM/kg. The infarct volume on FLAIR 48 hours after MCAO compared to lesion volume on DWI showed a significantly smaller ratio in the GV1001-treated group. GV1001-treated rats exhibited better behavioral functions than the saline-treated rats. Treatment with GV1001 increased the viability, proliferation, and migration of the OGD/R-injured NSCs. Free radicals were significantly restored by treatment with GV1001. These neuroprotective effects of GV1001 have also been demonstrated in OGD/R-injured cortical neurons. Conclusions The results suggest that GV1001 has neuroprotective effects against IRI in NSCs, cortical neurons, and the rat brain. These effects are mediated through the induction of cellular proliferation, mitochondrial stabilization, and anti-apoptotic, anti-aging, and antioxidant effects.